Connected markets through global real estate investments. (23rd May 2020) - Zhu, Bing; Lizieri, Colin
Abstract: This study focuses on the possibility of higher risk in commercial real estate markets due to the "linked ownership" network, which is measured by the common holdings of properties in different urban real estate markets by the same investor. Using data from 2007 to 2016, our results show that commonality in ownership can explain the significant comovement in international office market performance and add additional information to other matrices constructed by geographic distance, mergers and acquisitions capital flow, currency unit, and even overlapping occupiers located in those cities. The transmission mechanism is most pronounced and persistent during the global financial crisis period.